FUNCTIONING OF NO-SYNTHASE IN THE PERIPHERAL BLOOD LEUKOCYTES IN PATIENTS WITH ACNE VULGARIS - Lavryk, H.S.; Korniychuk, O.P.; Fedorovych, Z.Ya.; Vorobets, Z.D. (World of Medicine and Biology, 2018)
The role of staphylococci in the pathogenesis of acne is highlighted. The proliferation of the skin conditionally pathogenic microflora increases the release of inflammatory mediators and contributes to the development of the inflammatory process. Nitrogen oxide is a universal molecule that is involved in the regulation of many processes in human skin. The presence of several isoforms of NOS causes the formation of various concentrations of nitrogen oxide in different conditions, different cell types. The complexity of the mechanisms implementing the action of NO is the multi-directional activity of NO in the course of pathological processes. The regulatory factor is the activity of NO-synthase, and possibly arginase, which is in complex interactions with different cells and cytokines. The expression of constitutive NOS is necessary for normal functioning of the skin to ensure distribution of blood flow in the dermis and maintain the balance of renewal and aging of the skin cells. The lack of iNOS expression in physiological conditions indicates the need for small doses of NO to maintain balance. However, with different pathological processes, there is no definite positive or negative effect under the conditions of the same concentration of NO. For example, with allergic inflammation, high NO content provides support for eosinophilic inflammation, tissue swelling, and on the other hand, it inhibits histamine secretion by mast cells. Positive effects of nitric oxide are studied for their possible use for therapeutic purposes. The best effect after treatment has been established in those patients with acne, the skin of which has been isolated from the biofilm form of S. aureus, and to a lesser extent in patients with planktonic form of S. aureus. As is known, the formation of films is considered as an additional factor of the pathogenicity of microorganisms [6], and the importance of which increases in the event of a decrease in reactivity of the immune system. Being included into the mechanisms of inflammation, nitrogen oxide performs both proinflammatory and anti-inflammatory role. This is due to the fact that the development of inflammation is determined by the generation of nitrogen oxide synthesized with the participation of an inducible NOS. At the same time, NO synthase controls the biosynthesis of interleukins IL-4, IL-11, IL-13, which belong to inflammatory reaction inhibitors. Since the data we receive show that the activity of the inducible isoform NO-synthase in leukocytes with acne, both in planktonic and film-forming forms, grows by more than 50 times, which causes nitrosative stress, it can be assumed that the activity of this enzyme can serve as a marker indicator that characterizes the activity of the pathological process and the efficacy of acne treatment. The changes of endothelial and inducible NO-synthase activity of blood leukocytes of the patients with acne before and after treatment were studied. It has been found that the activity of endothelial isoform NO-synthase is significantly increased with respect to control values for both forms of acne caused by Staphylococcus aureus and Staphylococcus epidermidis (plankton and film-forming). Increase in several dozen times the inducible NO-synthase of peripheral blood leukocytes in all patients for whom film-forming and planktonic staphylococci were taken from pustules has been recorded. Inducible isoform NO-synthase activity decreases relative to the control level after the treatment of acne that was complicated by the proliferation of S. aureus (plankton and film-forming form). Changes in the activity of NO-synthase can be used as a marker of the dynamics of acne vulgaris development and the effectiveness of therapy.